Chronic stress and functional health in older adults with concerns about falling: a study protocol of a randomized controlled trial with multicomponent exercise intervention (FEARFALL) - Britting, Sabine; Kob, Robert; Görlitz, Anja; Sieber, Cornel C.; Freiberger, Ellen; Rohleder, Nicolas (Trials, 2024)
Background: Maintenance of physical function, mobility, and independent living are important goals for older adults. However, concerns about falling (CaF) play a central role in the vicious cycle of CaF, inflammation, loss of muscle mass, and decreasing physical function ultimately resulting in negative health outcomes. CaF, like other states of chronic stress and anxiety, can be considered as enduring adverse stimuli affecting the stress systems and the inflammatory system. Therefore, the aim of this study is to investigate whether a reduction of CaF leads to a reduction of stress and therefore possibly reduces chronic low-grade inflammation. Understanding the role and directionality of the effects of inflammation on CaF increases our understanding of age-related loss of mobility and physical function. Methods: In this study, community-dwelling older adults, aged 70 years and older, will be randomly assigned to either a 4-month, multi-component intervention with exercise training and cognitive-behavioral components or to a sham control group with light stretching exercises, cognitive training, and educational health lectures. For the operationalization of specific CaF, the Falls Efficacy Scale—International will be used. Stress and related psychological symptoms will be monitored using established self-reports and by measuring salivary cortisol. Concentrations of C-reactive protein, interleukin 6, interleukin 10, and tumor-necrosis-factor-alpha, as well as gene expression of selected inflammatory transcripts, will be used as surrogate parameters of the inflammatory status at baseline, after the 4-month intervention and 8-month follow-up. Discussion: This study will be the first to test whether CaF are related with stress system activity or reactivity or with markers of inflammation in the context of a multi-component intervention with exercise training and cognitive-behavioral components addressing CaF. The reduction of specific CaF or general psychological symptoms should reverse alterations in stress systems, and / or slow down low-grade inflammation. Changes in activity, as well as psychological and biological pathways leading from CaF to muscle loss will be measured, to disentangle the individual contribution to sarcopenia, and to provide an additional pathway to break or slow-down the vicious cycle of CaF and sarcopenia. Trial registration: German Clinical Trials Register (DRKS): DRKS00029171. Registered 22 July 2022.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Chronic stress; Concerns about falling; Cortisol; Inflammation; Interleukin 6; Older adults; Perceived stress; Randomized controlled trial; Sarcopenia